2011
DOI: 10.5301/jn.5000038
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to treatment and hospitalization risk in hemodialysis patients

Abstract: Higher IDWG and higher serum levels of phosphorus independently increased the relative risk of hospitalizations in hemodialysis patients. With skipped and shortened dialysis sessions, higher serum potassium level was not associated with hospitalization risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 13 publications
0
16
0
1
Order By: Relevance
“…Considering laboratory parameters, controversy exists on gender association with chronic kidney disease–mineral bone disease parameters. In the present analysis, serum phosphorus control was better in females, probably due to more effective dialysis, which results in greater phosphorus clearance [ 22 ], better compliance with diet [ 23 ] and/or better adherence to phosphate binders [ 24 ]. It has been reported that not only high but also low serum phosphorus levels can be associated with unfavorable prognosis [ 25 ], while a clear association between hyperphosphatemia and increased cardiovascular disease has not been demonstrated in females [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering laboratory parameters, controversy exists on gender association with chronic kidney disease–mineral bone disease parameters. In the present analysis, serum phosphorus control was better in females, probably due to more effective dialysis, which results in greater phosphorus clearance [ 22 ], better compliance with diet [ 23 ] and/or better adherence to phosphate binders [ 24 ]. It has been reported that not only high but also low serum phosphorus levels can be associated with unfavorable prognosis [ 25 ], while a clear association between hyperphosphatemia and increased cardiovascular disease has not been demonstrated in females [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given the importance of adherence to treatment in hemodialysis patients, several studies have been carried out in various countries. García-Llana et al (24,25) in Spain and Oliveria et al (26) in Brazil investigated quality of life and adherence to treatment of these patients. However, a review of the related studies in Iran demonstrated that no study has comprehensively and simultaneously surveyed the life quality and adherence to treatment in these patients despite the important role of the effect of adherence to treatment on quality of life in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Health is a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity. [ 5 ] To maintain a general level of health, patients undergoing hemodialysis must follow the prescribed treatment regimen. Adherence to treatment plays an important role in the effectiveness of hemodialysis and health promotion in patients.…”
Section: Introductionmentioning
confidence: 99%